Tailoring structural inhomogeneities in metallic glasses to enable tensile ductility at room temperature. Issue 10 (December 2016) - Ma, E.; Ding, J.
Abstract : Metallic glasses boast high strength, but their low ductility has been a major concern. Here, taking a structural perspective and citing selected examples, we advocate purposely enhanced structural inhomogeneities, in an otherwise compositionally uniform and single-phase amorphous alloy, to promote distributed plastic flow. Four current tactics (the four R's) to improve deformability are highlighted, from the standpoint of structural, and consequentially mechanical, heterogeneities that can be tailored in the monolithic glassy state. Highly rejuvenated glass structures, coupled with restrained shear banding instability, lead to tensile ductility and necking, which is unusual for glasses at room temperature. Possibilities of strain hardening and strain rate hardening that are needed to stabilize uniform elongation are discussed. Innovative design and processing of amorphous metals, with internal structures tuned to facilitate flow, offer new possibilities in pushing the envelope of ductility accessible to these high-strength materials.